Shikhara (superstructure) of the Sadashiva Temple - Temples of India Project Team (Jio Institute, 2024)
The shikhara (superstructure) exhibits an integrated jala of chaitya arches but the beauty of the shikhara lies on its frontal face which depicts an arrangement of gavaksha (dormer window) arches topped by a kirtimukha (face of glory), along with a portrayal of elegantly carved makaras (crocodiles) and majestic faces of elephants on the sides. Additionally, floral motifs and shankhas (conch shells) are also used to decorate the frontal façade of the shikhara.